ILLNESS REPRESENTATION AND SELF-CARE ABILITY IN PATIENTS WITH CHRONIC DISEASE. (11th November 2018) - Rivera, E; Corte, C
Abstract: Aims: To determine whether one's set of beliefs about their chronic disease is associated with self-care ability, emergency room visits or hospitalizations. Methods: Using a cross-sectional design, patients with heart failure, COPD, and chronic kidney disease completed questionnaires in outpatient clinics. The Revised Illness Perception Questionnaire (IPQ-R) was used to measure perceptions about disease timeline, consequences, personal control, treatment control, understanding of the illness (coherence), disease pattern (cyclical), and emotions. Outcome variables included self-care ability and number of emergency room visits and hospitalizations in the last year. Disease severity was also measured. Latent profile analysis using IPQ-R subscale scores was used to identify subgroups. Subgroup differences were examined. Results: Participants included 187 adults (mean age 65 years, 46% male, 74% Black). We found three subgroups (stable, overwhelmed, and confident), each characterized by a unique illness representation profile. The subgroups did not differ demographically and were not disease-specific. The stable subgroup (few consequences, non-fluctuating pattern) had the fewest people hospitalized in the last year. The overwhelmed subgroup (many consequences, disease not well-understood, variable pattern, high negative emotion) had high hospitalizations and low self-care ability. The confident subgroup (high perceived control, well-understood) had the highest self-care ability, but hospitalizations were similar to the overwhelmed subgroup. Emergency room visits did not differ by subgroup. Conclusions: Within the chronic disease population, there are three subgroups that differ in their illness representation profiles and health outcomes. Findings suggest that assessing patients' beliefs about their chronic disease may have important implications for subgroup-specific interventions.